An Exploration of the Control of Micturition Using a Novel in Situ Arterially Perfused Rat Preparation - Sadananda, Prajni; Drake, Marcus; Paton, Julian; Pickering, Anthony E. (Frontiers in Neuroscience, 2011)
Our goal was to develop and refine a decerebrate arterially perfused rat preparation (DAPR) that allows the complete bladder filling and voiding cycle to be investigated without some of the restrictions inherent with in vivo experimentation (e.g. ease and speed of set up (30mins), control over the extracellular milieu and free of anaesthetic agents). Both spontaneous (naturalistic bladder filling from ureters) and evoked (in response to intravesical infusion) voids were routinely and reproducibly observed which had similar pressure characteristics. The DAPR allows the simultaneous measurement of bladder intra-luminal pressure, external urinary sphincter electromyogram (EUS–EMG), pelvic afferent nerve activity, pudendal motor activity and permits excellent visualisation of the entire lower urinary tract, during typical rat filling and voiding responses. The voiding responses were modulated or eliminated by interventions at a number of levels including at the afferent terminal fields (intravesical capsaicin sensitisation-desensitisation), autonomic (ganglion blockade with hexamethonium) and somatic motor (vecuronium block of the EUS) outflow and required intact brainstem/hindbrain-spinal coordination (as demonstrated by sequential hindbrain transections). Both innocuous (eg perineal stimulation) and noxious (tail/paw pinch) somatic stimuli elicited an increase in EUS-EMG indicating intact sensory feedback loops. Spontaneous non-micturition contractions were observed between fluid infusions at a frequency and amplitude of 1.4±0.9 per minute and 1.4±0.3mmHg, respectively, and their amplitude increased when autonomic control was compromised. In conclusion, the DAPR is a tractable and useful model for the study of neural bladder control showing intact afferent signaling, spinal and hindbrain co-ordination and efferent control over the lower urinary tract end organs and can be extended to study bladder pathologies and trial novel treatments.